Postbiotics Unveiled: Mechanistic Insights and Therapeutic Implications in Obesity. - Hari Om (Emerging Trends in Metabolites, 2026)
The burgeoning global obesity epidemic necessitates innovative therapeutic approaches, and postbiotics, bioactive compounds arising from microbial fermentation, have emerged as promising contenders in reshaping obesity management. This comprehensive review explores the multifaceted mechanisms by which postbiotics impact obesity, from modulating gut microbiota composition to influencing metabolic pathways and enhancing energy expenditure. The exploration of postbiotics is rooted in a deeper understanding of the gut–brain axis and bidirectional communication between gut microbiota and host physiology in history. Unraveling the intricate mechanisms reveals that postbiotics selectively inhibit undesirable bacteria and demonstrate remarkable modulation of the host’s immune response, neuropeptides involved in appetite regulation, and improvements in insulin sensitivity. The symphony of interactions underscores the potential of postbiotics to address the multifactorial nature of obesity, offering a nuanced and comprehensive strategy. Furthermore, the anti-inflammatory effects of postbiotics resonate throughout the host’s metabolic pathways, influencing immune modulation and improving insulin sensitivity. As clinical evidence supports the efficacy of postbiotics in weight management and improvements in metabolic parameters, considerations for personalized treatment approaches become imperative. Integrating postbiotics into obesity management strategies offers an additional layer of intervention, with healthcare professionals playing a pivotal role in promoting their adoption. Navigating future directions and challenges involves addressing gaps in knowledge, exploring synergies with other therapeutic approaches, and overcoming hurdles in translating postbiotic research into clinical practice. In conclusion, the potential of postbiotics in reshaping obesity treatment is substantial, offering a glimpse into a future where microbial-derived compounds play a pivotal role in promoting health and mitigating the global burden of obesity-related complications.
Keywords: Keywords: Body mass index; clinical studies; insulin resistance; metabolic disorders; probiotics